Prevalence and Risk of Potential Cytochrome P450–Mediated Drug-Drug Interactions in Older Hospitalized Patients with Polypharmacy. (March 2013) - Doan, Julie; Zakrzewski-Jakubiak, Hubert; Roy, Julie; Turgeon, Jacques; Tannenbaum, Cara
BACKGROUND: As rates of polypharmacy rise and medication regimens become more complex, the risk of potential cytochrome P450 (CYP)–mediated drug-drug interactions (DDIs) is a growing clinical concern for older adults. objective: To determine the prevalence of potential CYP-mediated DDIs in older hospitalized adults with polypharmacy and analyze the relationship between the number of drugs dispensed and the probability of these interactions in this high-risk population. METHODS: A prospective 16-week cohort study was conducted among consecutive new patients aged 65 years and older with polypharmacy (>5 drugs) admitted to a community hospital. The medication profiles of these patients were analyzed with a new multidrug cytochrome-specific software program. The prevalence of potential CYP-mediated DDIs was determined, with the probability calculated as a function of the number of medications dispensed using multivariate Poisson regression adjusted for age and sex. Comparative performance of the software program and a standard 2-drug alert program for detecting these DDIs was evaluated using the Wilcoxon-Mann-Whitney rank-sum test. Pharmacists' decisions to recommend medication adjustment based on the probability of CYP-mediated DDIs were recorded. RESULTS: The prevalence of potential CYP-mediated DDIs detected among 275 older adults with polypharmacy was 80%. The probability of at least 1 CYP-mediated DDI was 50% for persons taking 5–9 drugs, 81% with 10–14 drugs, 92% with 15–19 drugs, and 100% with 20 or more drugs. Addition of each medication to a 5-drug regimen conferred a 12% increased risk of a potential CYP-mediated DDI after adjustment for age and sex (OR 1.12; 95% CI 1.09–1.14). The multidrug software identified a median increase of 3 (95% CI 2.5–3.5) potential CYP-mediated DDIs per patient, compared to use of the standard 2-drug alert software. Pharmacists targeted patients for medication adjustment or close clinical monitoring in 23% of cases. CONCLUSIONS: The prevalence of potential CYP-mediated DDIs is high in geriatric patients with polypharmacy. The risk of DDIs increases as a function of the number of medications dispensed. Pharmacists' decision to intervene for potential CYP-mediated DDIs depends on clinical judgment in addition to the output from drug alert software programs, but may be facilitated by a single multicomponent, multidrug potential CYP-mediated DDI assessment.